Analisa Kebutuhan Sistem Proteksi Kebakaran Pada Gedung B Universitas Tribhuwana Tunggadewi Jl.Telaga Warna Tlogomas, Kota Malang - Suriaman, Edelbertus; Yurnalisdel, Yurnalisdel; Rahma, Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Fire protection systems are needed to minimize the impact and losses caused by fire, as it is a dangerous hazard that can have a significant negative impact on society. Building B of Tribhuwana Tunggadewi University has not fully complied with the Minister of Public Works Regulation No. 26/PRT/M/2008 on Technical Requirements for Fire Protection Systems in Buildings and the Environment, based on the findings of the previous fire safety system inspection. The fire protection system requirements of Building B of Tribhuwana Tunggadewi University were analyzed by considering the system requirements as well as the requirements for sprinklers, building hydrants, and evacuation routes in case of fire. Finding out what makes a building and whether a fire protection system is required is the purpose of this research. Data for this research was collected through visits to institutions, observations, interviews, assessment and measurement of fire safety systems, and literature studies. Afterwards, the research findings were examined and evaluated for conclusions. The fire safety equipment component has a weight value of 8.14 and a condition value of 8.00. This shows that the protection system of block B of Tribhuwana Tunggadewi University still has a poor utility component. A groundwater tank with a water capacity of 300 m3, a complete Hydrant box requires 72,000 liters of air, a Hydrant pillar requires 68,400 liters of air, and a sprinkler system requires 91,560 liters of air, according to the needs of the fire protection system analysis. The recommendations are intended to improve the fire safety system of building B of Tribhuwana Tunggadewi University.